If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying U + 26 = 77 Reorder the terms: 26 + U = 77 Solving 26 + U = 77 Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + U = 77 + -26 Combine like terms: 26 + -26 = 0 0 + U = 77 + -26 U = 77 + -26 Combine like terms: 77 + -26 = 51 U = 51 Simplifying U = 51
| 68+x=99 | | x^2+2*x+5=0 | | 37+x=48 | | 0=1.1x-.4 | | 28+g=31 | | T+76=83 | | N+98=117 | | x^2+8*x+16=0 | | 36+z=41 | | D+38=97 | | 2m+4n=7 | | T+51=87 | | 4x^2+35x+54=2x^2+21x+30 | | 51/45 | | 2x^2-10x=x^2-5x | | M+13=42 | | -9+9y+4-2y= | | D+1=1 | | 0=2.6x+5.5 | | 15=9a-3 | | y+6(2)=5 | | p2-1/x=8 | | Q-10=28 | | y+6(-1)=5 | | 16+5x=91 | | 3+7y=2y-7 | | 8x-21=3(x+8) | | 2-2n=8(n+4) | | 22x-7*2x-88=0 | | -6(x-3)=6x-42 | | 0=-16t^2+160t+6 | | (x+6)=10 |